2020
DOI: 10.22435/hsr.v23i1.2741
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Konsumsi Makanan Tinggi Natrium dengan Kejadian Hipertensi pada Buruh Tani di Wilayah Kerja Puskesmas Panti Kabupaten Jember

Abstract: A very heavy workload of farmers must be balanced with optimal food intake in both quantity and quality. The study aimed to identify the relationship between high sodium food consumption and the incidence of hypertension among farm workersat Public Health Center of Panti in Jember Regency. A cross-sectional study design was performed 248 of farmworkers using stratifi ed random sampling. A self-administered questionnaire was used to identify the sociodemography of farm workers. Food frequency questionnaires and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
0
11
0
6
Order By: Relevance
“…Six elderlies have a family history of hypertension. Aristi et al (2020) found that the frequency of consumption high sodium food is associated with the incidence of hypertension in the subjects studied. Older adults who are getting older tend to have difficulty in carrying out daily activities; this is caused by the decrease in cognitive function of the elderly (Wijayanti et al, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…Six elderlies have a family history of hypertension. Aristi et al (2020) found that the frequency of consumption high sodium food is associated with the incidence of hypertension in the subjects studied. Older adults who are getting older tend to have difficulty in carrying out daily activities; this is caused by the decrease in cognitive function of the elderly (Wijayanti et al, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…Ismuningsih (2013) stated that some foods have a significant role in increasing blood pressure, such as excessive intake of sodium, carbohydrates, protein, and fat 15 . Aristi et al, (2020) in Jember Regency reported that the frequent consumption of biscuits, salted fish, milk, coffee, tea, and food seasonings (MSG) was associated with the incidence of hypertension by 33.1%. The type of chips and fish often consumed have a highsodium, which can lead to the occurrence of the disease 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Aristi et al, (2020) in Jember Regency reported that the frequent consumption of biscuits, salted fish, milk, coffee, tea, and food seasonings (MSG) was associated with the incidence of hypertension by 33.1%. The type of chips and fish often consumed have a highsodium, which can lead to the occurrence of the disease 16 . This is in line with a study carried out in the coastal area, where the main occupation of the residents was fishing.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension in Indonesia is 33.4% [2], while in East Java province, it is 20.43% [3]. Farming communities have a high risk of health problems [4], including hypertension [5][6][7]. Hypertension among farmers in Indonesia has reached 36.1% [8].…”
Section: Introductionmentioning
confidence: 99%